Bilateral polymicrogyria associated with dystonia: A new neurogenetic syndrome?. Issue 10 (17th August 2020) - Andelman‐Gur, Michal M.; Leventer, Richard J; Hujirat, Mohammad; Ganos, Christos; Yosovich, Keren; Carmi, Nirit; Lev, Dorit; Nissenkorn, Andreea; Dobyns, William B.; Bhatia, Kailash; Lerman‐Sagie, Tally; Blumkin, Lubov
Abstract: The clinical presentation of bilateral perisylvian polymicrogyria (PMG) is highly variable, including oromotor dysfunction, epilepsy, intellectual disability, and pyramidal signs. Extrapyramidal features are extremely rare. We present four apparently unrelated patients with a unique association of PMG with dystonia. The clinical, genetic, and radiologic features are described and possible mechanisms of dystonia are discussed. All patients were female and two were born to consanguineous families. All presented with early childhood onset dystonia. Other neurologic symptoms and signs classically seen in bilateral perisylvian PMG were observed, including oromotor dysfunction and speech abnormalities ranging from dysarthria to anarthria (4/4), pyramidal signs (3/4), hypotonia (3/4), postnatal microcephaly (1/4), and seizures (1/4). Neuroimaging showed a unique pattern of bilateral PMG with an infolded cortex originating primarily from the perisylvian region in three out of four patients. Whole exome sequencing was performed in two out of four patients and did not reveal pathogenic variants in known genes for cortical malformations or movement disorders. The dystonia seen in our patients is not described in bilateral PMG and suggests an underlying mechanism of impaired connectivity within the motor network or compromised cortical inhibition. The association of bilateral PMG with dystonia in our patients may represent a new neurogenetic disorder.